Sintesis Senyawa Heksapeptida Siklik Analog Pipecolisporin (Pro-Lys-Pipe-Trp-β-Ala-Phe) dengan Metode Kombinasi Fasa Padat dan Fasa Larutan sebagai Kandidat Antimalaria - Fitriana Asni; Nety Kurniaty (UNISBA Press, 2022)
Abstract. Malaria is an infectious disease caused by protozoa of the genus Plasmodium and then transmitted to humans through the Anopheles mosquito. One of the natural peptides found in previous studies is cyclic hexapeptide (Pro-Leu-Pipe-Trp- -Ala-Ile) from endophytic fungi isolated from the roots of Tritikum sp and produced pipecolisporin isolation which has been proven to have antimalarial activity. In this study the cyclic hexapeptide analogue pipecolisporin (Pro-Lys-Pipe-Trp- -Ala-Phe) has been successfully synthesized using a solid phase combination method (Solid Phase Peptide Synthesis) and a solution phase with a strategy of using Fmoc protective groups, solid phase buffers namely 2-chlorotrityl chloride resin and coupling reagents namely HATU, HOAt, and DIPEA. A linear hexapeptide compound has been formed which is indicated by the results of characterization using a mass spectrophotometer with an m/z value of 959.4612 at the ion peak and also a cyclic hexapeptide compound has been formed which is indicated by an m/z value of 741.4842 at the peak of the molecular ion [M+H]. Abstrak. Malaria merupakan penyakit menular yang disebabkan oleh protozoa dari genus Plasmodium dan kemudian ditularkan ke manusia melalui nyamuk anopheles. salah satu peptida alami yang ditemukan pada penelitian sebelumnya adalah heksapeptida siklik (Pro-Leu-Pipe-Trp- -Ala-Ile) dari jamur endofit yang diisolasi dari akar Tritikum sp dan menghasilkan isolasi pipecolisporin yang sudah terbukti memiliki aktivitas antimalaria. Pada penelitian ini heksapeptida siklik analog pipecolisporin (Pro-Lys-Pipe-Trp- -Ala-Phe) telah berhasil disintesis dengan menggunakan metode kombinasi fasa padat (Solid Phase Peptide Synthesis) dan fasa larutan dengan strategi penggunaan gugus pelindung Fmoc, penyangga fasa padat yaitu resin 2-klorotritil klorida serta reagen pengkopling yaitu HATU, HOAt, dan DIPEA. Senyawa heksapeptida linear telah terbentuk yang ditandai dengan hasil karakterisasi menggunakan spektrofotometer masasa dengan nilai m/z 959,4612 pada puncak ion dan juga Senyawa heksapeptida siklik telah terbentuk yang ditandai dengan nilai m/z 741,4842 pada puncak ion molekul [M+H].